2020
DOI: 10.1002/ccr3.2824
|View full text |Cite
|
Sign up to set email alerts
|

Nonpuerperal breast abscess due to Prevotella bivia

Abstract: Contrary to puerperal abscess, nonpuerperal breast abscess is often caused by anaerobic bacteria; polymicrobial aerobic‐anaerobic infections are also frequent. Empiric first‐choice treatment with broad‐spectrum antibiotics should be considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 30 publications
1
7
0
Order By: Relevance
“…Table 2 summarizes previous reports of Prevotella bivia infections as published in PubMed. [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] Similar to our case, the case presented by Bekasiak et al involved a scrotal abscess and co-infection with a second bacterial genus. 11 Additionally, co-infection occurred in 7 cases, including 2 cases with Prevotella bivia and Streptococcus anginosus, a well-known species that produces an abscess.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Table 2 summarizes previous reports of Prevotella bivia infections as published in PubMed. [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] Similar to our case, the case presented by Bekasiak et al involved a scrotal abscess and co-infection with a second bacterial genus. 11 Additionally, co-infection occurred in 7 cases, including 2 cases with Prevotella bivia and Streptococcus anginosus, a well-known species that produces an abscess.…”
Section: Discussionsupporting
confidence: 88%
“…5 Prevotella bivia infections in humans are rare, with only 18 published cases in 44 years. [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] Since most Prevotella bivia strains are β-lactamase-positive, 24 clindamycin, amoxicillin/clavulanate, metronidazole, and imipenem are the recommended antibacterial agents. 21,25 However, antibiotic resistance varies across countries, 26 and it is unknown whether Prevotella bivia strains in Japan are β-lactamase positive.…”
Section: Introductionmentioning
confidence: 99%
“…While puerperal abscesses are usually caused by skin flora, non-puerperal breast abscesses are often caused by anaerobic bacteria, in addition to Staphylococcus and Streptococcus species. Polymicrobial aerobic-anaerobic infections are also frequent [ 1 , 2 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therapeutic regimens and a review of the literature will also be discussed. To our knowledge, this is the only documented case of nonpuerperal breast abscess caused by Prevotella bivia in the United States of America [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…Once thought to be relatively harmless with pathogenic potential only attributed to the toxigenic clostridia and Bacteroides fragilis, have emerged in major life-threatening infections including bacteremia, puerperal breast abscess and non-puerperal breast abscesses where they account from between 1-17% cases [9][10][11]. Boucher et al [10] reported P. bivia pure culture in a patient with non-puerperal breast abscess after flucloxacillin empiric therapy 500mg/6 hours for 2 days. AST results showed resistance to clindamycin but susceptible to amoxicillin-clavulanate, piperacillin-tazobactam, imipenem, and metronidazole.…”
Section: Introductionmentioning
confidence: 99%